The Value in Pursuing the EdD (Journal of School Administration Research and Development, 2019)
With the pressure to continue professional development in the P-12 environment, typically via additional educational degrees, many have exhausted the masters degree-level training and are looking at the doctoral level of degrees. However, considerations of the amount of time and effort involved in pursuing doctoral-level degrees, the financial costs of the work, and confusion around which type of degree to pursue, have combined to create barriers in moving forward. This article is meant to assist in making this decision by talking about the differences between PhD and EdD programs and by advocating for a choice of the EdD. The advantages and value of EdD programs are discussed.